Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1136/fn.86.2.f102
|View full text |Cite
|
Sign up to set email alerts
|

Follow up of a randomised trial of two different courses of dexamethasone for preterm babies at risk of chronic lung disease

Abstract: Objectives: To report 18 month outcome of a randomised trial of two courses of dexamethasone to prevent chronic lung disease of prematurity. Study design: Babies of birth weight 1250 g or less ventilated at 7 days of age were randomised to a 42 day reducing course (long) or a 3 day pulsed (pulse) course of dexamethasone. Growth, cardiovascular status, and respiratory and neurodevelopmental outcomes were assessed at 18 months. Results: Seventy six babies were enrolled. Nine died and three were lost to follow up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 28 publications
2
31
2
Order By: Relevance
“…Although our finding of no effect of postnatal dexamethasone on blood pressure is consistent with the findings of others, 19,21,35 antenatal exposure to steroids has been associated with elevated blood pressure in later life both in animal experiments 22,36,37 and in an observa- tional study in humans. 24 Posited explanations for the long-term effects of antenatal steroids on blood pressure include alterations in kidney development, such as reduced nephron number, and alterations in the developing renin-angiotensin system.…”
Section: Discussionsupporting
confidence: 92%
“…Although our finding of no effect of postnatal dexamethasone on blood pressure is consistent with the findings of others, 19,21,35 antenatal exposure to steroids has been associated with elevated blood pressure in later life both in animal experiments 22,36,37 and in an observa- tional study in humans. 24 Posited explanations for the long-term effects of antenatal steroids on blood pressure include alterations in kidney development, such as reduced nephron number, and alterations in the developing renin-angiotensin system.…”
Section: Discussionsupporting
confidence: 92%
“…Starting doses of DXM might have a greater effect on the integrity of the central nervous system than the cumulative doses of DXM. This hypothesis is supported by 2 randomized trials that reported comparable neurodevelopmental outcomes at 18 months between infants treated with similar starting doses (0.5 mg/kg/day) but different cumulative DXM doses [21,26]. …”
Section: Discussionsupporting
confidence: 60%
“…We previously reported results from our two-year follow-up study of dexamethasone treatment 9 and from other studies conducted in young children. [10][11][12][13][14][15][16][17][18][19][20][21] These studies indicated that early postnatal dexamethasone therapy might affect somatic growth and neurodevelopmental outcome. Since the results of two-year follow-up cannot always predict future morbidity, there is a compelling need for long-term follow-up.…”
mentioning
confidence: 99%